2014
DOI: 10.1016/j.energy.2014.10.056
|View full text |Cite
|
Sign up to set email alerts
|

Power production via North Sea Hot Brines

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Therefore, a project may decide to accept higher drilling costs and drill deep enough to produce electricity from the resource. Many studies have proposed using abandoned oil wells, or those that coproduce hot water, for geothermal schemes 58,59 . This negates the high costs and risk incurred from drilling, but is yet to be widely implemented.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a project may decide to accept higher drilling costs and drill deep enough to produce electricity from the resource. Many studies have proposed using abandoned oil wells, or those that coproduce hot water, for geothermal schemes 58,59 . This negates the high costs and risk incurred from drilling, but is yet to be widely implemented.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Auld et al [11] examined the power production potential for a suite of oilfields in the Northern North Sea (Brent Province), including the aforementioned Murchison Field. Here, the condensing fluid is the cold North Sea (approx.…”
Section: Power Generationmentioning
confidence: 99%
“…Auld et al [11] demonstrated that the six Brent Fields studied in detail could have produced more than 10 MW and one, Ninian, 31 MW (Figure 6). A comparison of the cost of the ORC system sized for 10 MW power generation showed that payback was between 3 and 4.5 years.…”
Section: Power Generationmentioning
confidence: 99%
See 2 more Smart Citations